A Peer Health Educator Program for Breast Cancer Screening Promotion: Arabic, Chinese, South Asian, and Vietnamese Immigrant Women's Perspectives - Joanne Crawford; Angela Frisina; Tricia Hack; Faye Parascandalo (Hindawi Limited, 2015)
This study explored Arabic, Chinese, South Asian, and Vietnamese immigrant women's experiences with a peer health educator program, a public health program that facilitated access to breast health information and mammography screening. Framed within critical social theory, this participatory action research project took place from July 2009 to January 2011. Ten focus groups and 14 individual interviews were conducted with 82 immigrant women 40 years of age and older. Qualitative methods were utilized. Thematic content analysis derived from grounded theory and other qualitative literature was employed to analyze data. Four dominant themes emerged: Breast Cancer Prevention focused on learning within the program, Social Support provided by the peer health educator and other women, Screening Services Access for Women centered on service provision, and Program Enhancements related to specific modifications required to meet the needs of immigrant women accessing the program. The findings provide insights into strategies used to promote breast health, mammography screening, and the improvement of public health programming. Perceived barriers that continue to persist are structural barriers, such as the provision of information on breast cancer and screening by family physicians. A future goal is to improve collaborations between public health and primary care to minimize this barrier.